H Hubungan Pengetahuan dan Personal Hygiene Dengan Kejadian Diare Pada Balita - Septi Adi Ningsih; Dian Utama Pratiwi Putri; Dwi Yulia Maritasari (An Idea Health Journal, 2024)
Diarrhea is an endemic disease that has the potential to cause Extraordinary Events and is still a contributor to the death rate in Indonesia, especially among children under five. This research aimed to determine the relationship between knowledge and personal hygiene with the incidence of diarrhea in toddlers in the working area of the Labuhan Ratu Health Center. This type of research is quantitative, using a cross-sectional research design. The sample in this study was 100 mothers with toddlers who were obtained from sample calculations using proportion estimation. Data was collected using a questionnaire, the data collection technique used purposive sampling, and the data was then analyzed using the chi-square test. The research showed that 50 toddlers had diarrhea in the last month. Most respondents' knowledge was not good 64 (64.0%), and most personal hygiene was not good 74 (74.0%). Based on the results of the chisquare test carried out on the knowledge variable, a p-value of 0.532 was obtained (< 0.05), then the results of the chi-square test carried out on the personal hygiene variable obtained a p-value of 0.043 (< 0.05). In conclusion, a significant relationship exists between personal hygiene and the incidence of diarrhea. Advice for mothers to actively attend or participate if there are outreach activities organized by health workers from the Community Health Center, especially education about preventing diarrhea.